2016
DOI: 10.1080/07448481.2016.1138477
|View full text |Cite
|
Sign up to set email alerts
|

Attention-deficit/hyperactivity disorder–specific stimulant misuse, mood, anxiety, and stress in college-age women at high risk for or with eating disorders

Abstract: Objective To examine the misuse of ADHD-specific stimulants in a college population at high risk for or with clinical or subclinical eating disorders. Participants 448 college-age women ages 18–25 at high risk for or with a clinical or subclinical eating disorder. Methods Participants completed assessments of stimulant misuse and psychopathology from September 2009 - June 2010. Results Greater eating disorder pathology, objective binge eating, purging, eating disorder-related clinical impairment, depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 43 publications
0
15
0
1
Order By: Relevance
“…18,31 Some studies have found that individuals who report NMU are more likely to have eating disorders. 51,59,109 For example, among 707 college students without a prescription for stimulants, respondents who used stimulants for weight loss had more symptoms of eating disorders than those who did not. 59 Motivations.…”
Section: Risk Factors and Motivations For Nmu Of Stimulantsmentioning
confidence: 99%
“…18,31 Some studies have found that individuals who report NMU are more likely to have eating disorders. 51,59,109 For example, among 707 college students without a prescription for stimulants, respondents who used stimulants for weight loss had more symptoms of eating disorders than those who did not. 59 Motivations.…”
Section: Risk Factors and Motivations For Nmu Of Stimulantsmentioning
confidence: 99%
“…Moreover, one study found that increased stimulant misuse was present within a specific group of college-age women at risk for or with a clinical or subclinical eating disorder (Gibbs et al, 2016). These findings highlight possible gender differences in patterns of stimulant misuse that require further investigation (Wu & Schlenger, 2003); to date, however, these possible differences in use characteristics have not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Weight control is a common motivation for prescription stimulant misuse among women . Indeed, Gibbs et al found that 17% of women who misused prescription stimulants did so primarily as a means of controlling their weight/body shape.…”
Section: Misuse Of Prescription Stimulant Medication Among Womenmentioning
confidence: 99%